2014
DOI: 10.2147/opth.s69710
|View full text |Cite|
|
Sign up to set email alerts
|

Intracameral phenylephrine and ketorolac injection (OMS302) for maintenance of intraoperative pupil diameter and reduction of postoperative pain in intraocular lens replacement with phacoemulsification

Abstract: BackgroundThe purpose of this study was to evaluate the effect of OMS302 on intraoperative pupil diameter and early postoperative ocular pain when administered during intraocular lens replacement surgery.MethodsFour hundred and six patients (406 study eyes; 202 in the OMS302 group and 204 in the placebo group) were entered into this randomized, double-masked, placebo-controlled, multicenter Phase III study, which was conducted at 15 centers in the USA and the Netherlands. The patients received OMS302 (60.75 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…In November of 2013, the combined results of the two Phase III clinical trials (both including >400 participants) were presented as a scientific poster at the American Academy of Ophthalmology Annual Meeting in New Orleans 91. The results showed that OMS302 maintained a necessary pupil diameter throughout the IOL replacement procedure, while the placebo group showed progressive constriction ( P <0.00001).…”
Section: Early Research On Ketorolac/phenylephrine or Oms302mentioning
confidence: 99%
“…In November of 2013, the combined results of the two Phase III clinical trials (both including >400 participants) were presented as a scientific poster at the American Academy of Ophthalmology Annual Meeting in New Orleans 91. The results showed that OMS302 maintained a necessary pupil diameter throughout the IOL replacement procedure, while the placebo group showed progressive constriction ( P <0.00001).…”
Section: Early Research On Ketorolac/phenylephrine or Oms302mentioning
confidence: 99%
“…Intraoperative miosis can affect visualization of the surgical field; increase the risk of complications, inflammation, and postoperative pain; and reduce patient satisfaction 1. Failure to maintain an adequate pupil diameter can increase the difficulty of the procedure and increase the risk of intraoperative and postoperative complications 2. Intraoperative pupil constriction can make every step of a cataract procedure more challenging and problematic by limiting the size of the capsulorhexis, increasing the risk of iris injury, and reducing visualization for phacoemulsification and lens implantation 3.…”
Section: Introductionmentioning
confidence: 99%
“…Maintenance of mydriasis throughout surgery to allow for better visualization of the surgical field and a greater working area within the pupil is crucial for successful surgical outcomes 4. Postoperative pain is associated with clinical outcomes and patient well-being, preventing or reducing postoperative pain can improve patient satisfaction 1,2. Reduction of postoperative pain is important because patient expectations are high in modern cataract surgery and ocular pain, and discomfort represents a common cause of patient dissatisfaction 5…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations